PREVALENCE OF DIABETES MELLITUS AND THEIR COMPLICATION IN ABO BLOOD GROUP (The Research of Medical Science Review, 2025)
Background: Diabetes mellitus is a global epidemic affecting around 463 million individuals worldwide. It can lead to complications in various organs like the heart, kidneys, and eyes. Recent studies suggest that diabetes might also influence ABO blood grouping, potentially causing problems in blood transfusions and organ transplants. ABO blood grouping compatibility is essential, as any variation can lead to immune reactions and complications. High blood sugar levels in diabetes could impact ABO antigen expression, increasing the risk of immune reactions and transplant rejection. Understanding the link between diabetes and ABO blood grouping is vital for safe medical procedures in diabetic patients. Methodology: A cross-sectional study was conducted in Timergara dir lower Pakistan to explore the relationship between blood group system and diabetes by recruiting 287 patients 111 male and 176 females from DHQ Hospital Timergara affiliated with Timergara Medical College. Ethical approval was granted and informed written consent was obtained from all participants after explaining the study's potential risk and benefits. Comprehensive clinical examinations were conducted, recording age, lifestyle, and diabetes-related complications on standardized forms. Blood samples were collected following protocols, with ABO blood groups determined via standard agglutination method and blood glucose level measured using the GOD-POD method with the glucose humen kit. Data were statistically analyzed to investigate potential association between diabetes mellitus and the ABO blood group system using a one-sample chi-square test to assess the significance of any observed correlation between specific blood groups and diabetes incidence in the population. Results; This study involved 287 patients (38.7% males, 61.3% females) with 119 diabetic and 168 non-diabetic individuals. The distribution of diabetic patients across different blood groups showed a statistically significant association (p < 0.05). Additionally, the study found a highly significant association between diabetes and microvascular complications, with retinopathy being the most common complication. Conclusion; individuals with B blood group showed a higher susceptibility to diabetes retinopathy was the most prevalent microvascular complication our analysis confirmed the association between diabetes and the ABO blood group and microvascular complications.